Brand Image, Service Quality, and Product Differentiation: Building Customer Satisfaction - Siswati, Endang (Eastasouth Institute, 2025)
This quantitative study was carried out at the Bicopi Cafe in Surabaya with the goal of analyzing the impact of difference, brand image, and service quality on customer happiness. Eighty respondents were selected from among Bicopi's clientele. Multiple linear regression was used for data analysis with SPSS 25.0 assistance once the validity and reliability of the gathered data were confirmed. The results showed that customer satisfaction is significantly and favorably impacted by service quality. Similarly, when compared to service quality and product difference, brand image is the most prominent characteristic and has a considerable and positive impact on consumer satisfaction. In the meantime, consumer happiness at Bicopi Cafe in Surabaya is not substantially impacted by the differentiation variable.